Cannabis Use for Restless Legs Syndrome and Uremic Pruritus in in patients treated with maintenance dialysis: A Survey. (September 2020) - Samaha, Daniel; Kandiah, Trisha; Zimmerman, Deborah
Background: Restless legs syndrome (RLS) and uremic pruritus reduce the quality of life in patients with end-stage kidney disease (ESKD) and current treatments are often insufficient. There is an increasing interest in using cannabinoids for symptom management, and preliminary evidence suggests cannabinoids may help alleviate RLS and pruritus. Objectives: (1) To assess the frequency and severity of RLS and pruritus in our ESKD population with the current treatment options, (2) to estimate patient use of cannabinoids for these symptoms, and (3) to determine interest in participating in future trials to treat RLS and/or pruritus. Design: Survey. Patients: Adult prevalent patients with ESKD treated with dialysis at the Ottawa Hospital. Measurements: International RLS Study Group Rating Scale and visual analogue scale for symptom severity of RLS and pruritus, respectively. Methods: Eligible patients with ESKD treated at the Ottawa Hospital were invited to complete a survey to identify symptoms and severity of RLS and pruritus using validated scales, cannabis use for management, and interest in future trials. Basic demographic statistics to describe the study population and results were used. Results: Sixty-nine percent (192 of 277) of eligible patients completed the surveys, 35 declined participation, and 50 surveys were not returned. Eighty-six (45%) and 129 patients (67%) reported symptoms of RLS and pruritus, respectively. Only 18 previously symptomatic patients were relieved with current treatment. Fifteen patients reported cannabis use for symptoms; 9 noted improvement. Most (>2 of 3) symptomatic patients were interested in participating in a future trial. Limitations: Single-center study in a tertiary-care hospital in Canada limiting generalizability. Quoted prevalence of symptoms is dependent on survey return. Conclusions: A large proportion of ESKD patients suffer from RLS and/or pruritus, most of which are not relieved by existing treatments. Few patients reported trying cannabis to decrease their symptoms despite legalization. This study confirms strong patient interest for future trials regarding cannabis for symptom relief. Trial Registration: Not applicable.